PENINGKATAN KUALITAS SDM: PRASYARAT KETAHANAN EKONOMI DALAM ERA GLOBALISASI - I Komang Gde Bendesa (PIRAMIDA, 2005)
Information technology has made globalization in all aspects of life spread all over the world faster. As a result competition is becoming tighter. Education is one of ways to face this reality. The government and society have to pay more attention at some aspects that can increase the quality of education, such as investment on education, health, research and development, and technology. In addition, education must be treated as investment instead of consumption. The increase of education will be able to overcome the impact of globalization, hence to enhance the economy.